Synthesis and physicochemical characterization of a novel adsorbent based on yttrium silicate: A potential material for removal of lead and cadmium from aqueous media. Issue 4 (August 2020) - Litrenta Medeiros, Vinicius; de Araujo, Leandro Goulart; Rubinho Ratero, Davi; Silva Paula, Alex; Ferreira Molina, Eduardo; Jaeger, Christian; Marumo, Júlio Takehiro; Nery, José Geraldo
Graphical abstract: Highlights: Novel yttrium metallosilicate was synthesized by sol-gel chemistry. XRD, FT-IR, 29 Si MAS-NMR, 89 Y MAS-NMR data indicated a mixed framework structure. High adsorption for Pb 2+ (94 %) and Cd 2+ (74 %) from aqueous medium was observed. Pseudo-First Order (PFO) and Pseudo-Second Order (PSO) fitted the kinetic curves. Kinect data indicate chemisorption of lead onto the yttrium metallosilicate. Abstract: A new metallosilicate based on yttrium was synthesized and characterized by XRD, FT-IR, 29 Si MAS-NMR, and 89 Y MAS-NMR. The mixed framework of the material was confirmed by the detection of distinct chemical shift groups using 29 Si MAS-NMR (at -82 to -87 ppm, -91 to -94 ppm, -96 to -102 ppm, and -105 to -108 ppm), as well as four distinct chemical shifts in the 89 Y MAS-NMR spectrum (at -89, -142, -160, and -220 ppm). Adsorption and kinetic analyses indicated the potential of the new material for the removal of lead and cadmium from aqueous media. The adsorption results for lead indicated that dynamic equilibrium was reached after five hours, with total lead removal of around 94 %, while for cadmium it was reached in the first hour, with total cadmium removal of around 74 %. The adsorptions of lead and cadmium were modeled using pseudo-first order (PFO) and pseudo-second order (PSO) kinetic models. Although both models provided high R 2 values (0.9903 and 0.9980, respectively), the PSO model presented a much lower χ 2 red value (4.41 × 10−4), compared to the PFO model (2.12 × 10−3), which indicated that the rate-limiting step was probably due to the chemisorption of lead from the solution onto the yttrium-based metallosilicate.